2010
DOI: 10.1016/s2255-4971(15)30306-2
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fracture: Post-Operative Evaluation of Clinical and Functional Outcomes

Abstract: Objective: To evaluate the clinical and functional outcomes from patients undergoing surgery to treat hip fractures, with regard to the ASA score and time spent waiting for definitive surgical treatment. Method: Over a one-year period, 154 patients with hip fractures, aged 65 years and over, underwent operations. Data on the preoperative ASA score and the time spent waiting for the operation were obtained. Two years after the operation, Zuckerman‘s Functional Recovery Score (FRS) questionnaire was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
(56 reference statements)
1
10
0
3
Order By: Relevance
“…The Lee score can be compared to another presurgical evaluation tools, such as the American Society of Anesthesiologists (ASA) score. A Brazilian study 14 has shown a correlation between this latter method and mortality after hip fracture surgical correction. 14 Both consider criteria which, isolated, are significant in the onset of fatalities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Lee score can be compared to another presurgical evaluation tools, such as the American Society of Anesthesiologists (ASA) score. A Brazilian study 14 has shown a correlation between this latter method and mortality after hip fracture surgical correction. 14 Both consider criteria which, isolated, are significant in the onset of fatalities.…”
Section: Discussionmentioning
confidence: 97%
“…A Brazilian study 14 has shown a correlation between this latter method and mortality after hip fracture surgical correction. 14 Both consider criteria which, isolated, are significant in the onset of fatalities. Cardiac insufficiency, for instance, is one of the cardiac conditions with the highest mortality rate in non-cardiological procedures, as well as aortic stenosis and pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 97%
“…Validated scoring scales provide valuable information about the patients’ progress after proximal femur fracture management, and can show which procedure has the best outcome [7,8]. Modified Harris Hip Score (modified HHS) has acceptable validity to assess functional and clinical outcomes after proximal femur fracture management [9,10].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Subsequently, another study involved 154 fractures of the proximal third of the femur treated surgically and used the Hip Function Recovery Score questionnaire ( Appendix A ) created by Zuckerman et al 7 , 8 , 9 It consists of 11 questions related to the activities of daily living: four related to independence in basic activities, six to instrumental activities and one to mobility. 10 However, this questionnaire was used in its original version, in the English language, after its literal translation. 10 …”
Section: Introductionmentioning
confidence: 99%
“… 10 However, this questionnaire was used in its original version, in the English language, after its literal translation. 10 …”
Section: Introductionmentioning
confidence: 99%